IMPLEMENTATION OF APPLIED RESEARCH INTO THE STUDY PROCESS WHEN TRAINING THE PROFESSIONALS OF ENVIRONMENT PROTECTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The studies on the college level are directed towards practical training, thus the applied research executed in colleges may be involved into the study process as one of the research teaching methods. This research not only ensures the link between theory and practice, but also trains general abilities of the students and personal characteristics highly valued by the employers. The article analyses the experience of Ecology Department to implement the applied researches “Evaluation of Water Quality in Shaft Wells” and “Determination of Nitrogen Dioxide Concentration in the Environment Air by Applying the Method of Passive Sampling” into the subjects of Environment Protection and Environment Monitoring. It discusses the way the studies are held, in what ways the students take part in research, how they evaluate it, what problems they face.